KEAKURATAN KODE DIAGNOSIS DENGAN ICD-10 DI PUSKESMAS PENGASIH I DAN PENGASIH II - laili rahmatul ilmi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Background: The implementation of Electronic Medical Record (EMR) in Puskesmas Kulon Progo as a tool to communicate and coordinate between health practitioner related with patient’s status. On the other hand, it as a monitoring and evaluating morbidity surveillance. The accurateness of Code Diagnosis by using ICD-10 can improve the quality of itObjective: to evaluate the accurateness of code diagnosis to improve the quality of EMR data.Methode: descriptive study with a qualitative approach by using secondary data from EMR system with using cross sectional desaign. The object that is used of 234 code diagonosis from Pengasih I and Pengasih II health centres, the participants as an interviewee which is they divided from nurse, a midewife as the officer who filled directly into the EMR diagnosis code in SIMPUS. Data collection techniques used were interview, observation and study document by using EMR data from SIMPUSResult: 234 code diagnosis from EMR data between Pengasih I and Pengasih II are analysed based on ICD-10, there are code diagnosis from EMR in Pengasih I accurateness 30 (26%), not accurateness 87 (74%). In Pengasih II accurateness 35 (30%) and not accuratness 82 (70%). The factors that lead to coding diagnosis inaccuracies are element man, method and machineConclusion: The results suggest that although they already used the EMR, the quality of the data especially related to the coding diagnosis still low